Marcas de experiências no trabalho socioeducativo: narrativas camaradas da formação profissional - Gorgatti, Viviane [UNIFESP] (2017)
Instigated by the theme of a professional formation that does not serve only to pragmatic purposes, meeting utilitarian, production-based and reproductive demands, this project investigates the formation as an alive experience, composed of processes which constitute singular ethical-political positions. Its objective is to investigate imprints from experiences produced in the formative processes in the socio-educational work at the NGO Centro Camará de Pesquisa e Apoio a Infância e Adolescência which is based in the city of São Vicente, in São Paulo state. We start from the hypothesis that the formative processes that are constitutive of singular ethical-political positions are the learnings that occur in alive and collective experience having the act (thought/action) as producer of subjectivities and of imprints which can be noticed in the positionings when facing the work. The research subjects have been fourteen ex-interns and social educators which have been imprinted during their professional paths by the experience in the institution. A participatory methodology was used, in which the participants were invited to produce narratives that included meaningful scenes from their trajectory in Camará. The analysis of this material produced a text, written by the researcher in which the concepts of dimensions of forms and forces derived from cartography gave support to the display of the common experience that is present in the imprints that were previously referred. This text was a trigger to the second stage of the process, in which a new, now collective, analysis was produced in a live meeting of the subjects and the researcher, shaped as a talk circle. A third stage was performed: the analysis of the whole research process in which meaningful excerpts from the narratives, from the collective analysis during the talk circle, from the researcher’s memory and from this thesis writing experience itself were discussed. During the investigation of the imprints produced in the formation processes the following aspects were noticiable: the inverted perspective as ethical-political orientation; the construction of the common field as a place of collective production, having the happening as its highway and reference of the the work by itinerancies; the body as the place for holding the attention; and the work-existence as openness to inventive learning.